1995
DOI: 10.1146/annurev.bi.64.070195.002251
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activities of Group Ii Introns

Abstract: Group II introns are found in eubacteria and eubacterial-derived, organellar genomes. They have ribozymic activities, by which they direct and catalyze the splicing of the exons flanking them. This chapter reviews the secondary structure and known tertiary interactions of the ribozymic component of group II introns in relation to the problems of specifying splice sites and building a catalytic core. We pay special attention to the relationship between the transesterification and hydrolytic modes of initiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
551
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 543 publications
(559 citation statements)
references
References 0 publications
5
551
1
2
Order By: Relevance
“…The ⌬GA mutation dramatically inhibits the trans splicing reaction, and the DM abolishes splicing under transesterification conditions+ Note, however, that the splicing defects of all four substrates (including DM) are partially rescued under hydrolysis conditions (data not shown)+ For this set of experiments, we also confirmed that the D5 G3U and ⌬GA mutations do not exert their ef- -7), and the control was incubated for 120 min (lane 8)+ D: Same as C, except the DM RNA was the substrate+ fects by increasing the reversal of the second step of splicing (data not shown)+ Whether group II introns harbor one or two catalytic sites is a matter of debate+ If group II introns harbor two distinct catalytic sites, then one might expect to find certain intron nucleotides that are essential for the first step of splicing and other nucleotides that are essential for the second step+ This topic was reviewed by Michel and Ferat (1995), who concluded that no evidence exists indicating that any particular group II intron nucleotide participates in catalysis of only one of the two steps of splicing+ Although the fact remains that no intron nucleotide has been found to participate exclusively in only one of the two steps of splicing, our results with the ⌬GA mutation are particularly striking in this regard+ Point mutations that primarily affect the second step of group II intron splicing are rare+ Furthermore, to see the effects of such mutations on the second step of splicing, it is typically necessary to study the mutations in the context of a precursor with a short (13 nt) 59 exon (Jacquier & Michel, 1990;Jacquier & Jacquesson-Breuleux, 1991;Chanfreau & Jacquier, 1993)+ The short precursor is used because, even in the absence of point mutations, the second step of splicing is known to be slow when short transcripts are used+ In the past, the effects of second-step specific mutations have only been seen in the context of the short precursor+ In contrast, we find that even in the context of the full-length precursor, the ⌬GA mutation dramatically slows the second step of splicing+ Thus, to our knowledge, the ⌬GA mutation has the most dramatic effect on the second step of splicing of any point mutation that has been studied+ Why does deletion of the GA dinucleotide specifically slow the second step of splicing? We have recently found that group II introns can be released by an alternative pathway that results in release of the intron as a true circle in which the first residue of the intron is joined to the last residue by a 29-59 phosphodiester bond (H+L+ Murray et al+, submitted)+ We hypothesized that the ⌬GA mutation slows the second step of splicing because it stimulates the use of the terminal uridine residue of the intron as an alternative branch site and that, when the alternative branch site is used, the second step of splicing is inhibited+ However, primer extension analysis of the intron/E3 intermediate showed no evidence that the terminal uridine is used as an alternative branch site in the mutant substrate (data not shown)+ As an alternative model, we considered the possibility that the ⌬GA mutation inhibits the conformational change that has been shown to occur between the first and second steps of splicing+ The conformational change was first described by Chanfreau and Jacquier (1996), who showed that mutations that block the conformational change also speed the reversal of the first step of splicing + As described above, we find that the ⌬GA mutation does not speed the reversal of the first step of splicing+ Thus, it is unlikely that the mutation affec...…”
Section: Effect Of Point Mutations On the Second Step Of Splicingmentioning
confidence: 99%
“…The ⌬GA mutation dramatically inhibits the trans splicing reaction, and the DM abolishes splicing under transesterification conditions+ Note, however, that the splicing defects of all four substrates (including DM) are partially rescued under hydrolysis conditions (data not shown)+ For this set of experiments, we also confirmed that the D5 G3U and ⌬GA mutations do not exert their ef- -7), and the control was incubated for 120 min (lane 8)+ D: Same as C, except the DM RNA was the substrate+ fects by increasing the reversal of the second step of splicing (data not shown)+ Whether group II introns harbor one or two catalytic sites is a matter of debate+ If group II introns harbor two distinct catalytic sites, then one might expect to find certain intron nucleotides that are essential for the first step of splicing and other nucleotides that are essential for the second step+ This topic was reviewed by Michel and Ferat (1995), who concluded that no evidence exists indicating that any particular group II intron nucleotide participates in catalysis of only one of the two steps of splicing+ Although the fact remains that no intron nucleotide has been found to participate exclusively in only one of the two steps of splicing, our results with the ⌬GA mutation are particularly striking in this regard+ Point mutations that primarily affect the second step of group II intron splicing are rare+ Furthermore, to see the effects of such mutations on the second step of splicing, it is typically necessary to study the mutations in the context of a precursor with a short (13 nt) 59 exon (Jacquier & Michel, 1990;Jacquier & Jacquesson-Breuleux, 1991;Chanfreau & Jacquier, 1993)+ The short precursor is used because, even in the absence of point mutations, the second step of splicing is known to be slow when short transcripts are used+ In the past, the effects of second-step specific mutations have only been seen in the context of the short precursor+ In contrast, we find that even in the context of the full-length precursor, the ⌬GA mutation dramatically slows the second step of splicing+ Thus, to our knowledge, the ⌬GA mutation has the most dramatic effect on the second step of splicing of any point mutation that has been studied+ Why does deletion of the GA dinucleotide specifically slow the second step of splicing? We have recently found that group II introns can be released by an alternative pathway that results in release of the intron as a true circle in which the first residue of the intron is joined to the last residue by a 29-59 phosphodiester bond (H+L+ Murray et al+, submitted)+ We hypothesized that the ⌬GA mutation slows the second step of splicing because it stimulates the use of the terminal uridine residue of the intron as an alternative branch site and that, when the alternative branch site is used, the second step of splicing is inhibited+ However, primer extension analysis of the intron/E3 intermediate showed no evidence that the terminal uridine is used as an alternative branch site in the mutant substrate (data not shown)+ As an alternative model, we considered the possibility that the ⌬GA mutation inhibits the conformational change that has been shown to occur between the first and second steps of splicing+ The conformational change was first described by Chanfreau and Jacquier (1996), who showed that mutations that block the conformational change also speed the reversal of the first step of splicing + As described above, we find that the ⌬GA mutation does not speed the reversal of the first step of splicing+ Thus, it is unlikely that the mutation affec...…”
Section: Effect Of Point Mutations On the Second Step Of Splicingmentioning
confidence: 99%
“…Group II intron self-splicing is generally thought to proceed through a series of two transesterification reactions (Michel & Ferat, 1995)+ Much like nuclear splicing (Padgett et al+, 1984;Ruskin et al+, 1984), the 29-hydroxyl group on a bulged adenosine within the intron has been observed to act as the nucleophile during the first step of splicing+ This adenosine is located in Domain 6 (D6) of group II introns, which is a short hairpinloop structure located upstream of the 39-splice site (Fig+ 1)+ During the second step of splicing, the exons are ligated and the branched intron is released as a lariat-shaped molecule (Peebles et al+, 1986;Schmelzer & Schweyen, 1986;van der Veen et al+, 1986)+ Given this mechanistic pathway, the bulged adenosine of group II introns would seem to be of primary importance for splicing+ However, certain group II introns lack a bulged adenosine in Domain 6 (Michel et al+, 1989)+ In addition, there is considerable evidence that splicing can proceed through an alternative pathway in which the 59-splice site is cleaved by hydrolysis rather than transesterification during the first step (van der Veen et al+, 1987;Jarrell et al+, 1988;Daniels et al+, 1996;Podar et al+, 1998)+ Although a branch-point is not strictly required for self-splicing, lariat formation represents an important, and perhaps the major, pathway for selfsplicing+ Nonetheless, it is not clear how the branchpoint adenosine is recognized, or if the bulged structure is important for transesterification+…”
Section: Introductionmentioning
confidence: 99%
“…We have cloned one of the members of this peculiar subset of intron sequences, as well as a closely related, but apparently ''normal'' intron inserted at the same genomic site in another host, and we now show that the self-splicing reaction of the former (but not latter) molecule is initiated by hydrolysis, resulting in excision of the intron in linear form, rather than by transesterification, which generates a lariat structure (as is normal for group II introns) (for review, see Michel and Ferat 1995). More generally, we propose that the loss of the ability to form a branched structure should be regarded as an ultimate consequence of the recently documented (Mullineux et al 2010) evolutionary conversion of some mitochondrial group II introns into DNA transposons (the class II mobile elements of Wicker et al ½2007 that move at the DNA level, contrary to retrotransposons that change location as RNA).…”
Section: Introductionmentioning
confidence: 70%
“…As inferred from experiments in which phosphodiester bonds were replaced by phosphorothioates (Steitz and Steitz 1993; also, for review, see Michel and Ferat 1995;Jacquier 1996), the geometry of the reactive bond in the branching step must differ from the one that prevails during reversal of exon ligation, and also in 59 hydrolysis. Introns in which the end of the IBS1 sequence is not directly connected to the GUGCG consensus sequence are unable to catalyze branching, probably because interactions between the ribozyme and nucleotides bordering the 59 splice site on both its 59 and 39 sides are necessary to drive the phosphodiester bond between the intron and 59 exon into the appropriate, presumably highly constrained conformation required for firststep transesterification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation